PENGARUH IKLAN BUMBU PENYEDAP ROYCO TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN IBU RUMAH TANGGA PADA KELURAHAN SIDOMULYO TIMUR KECAMATAN MARPOYAN DAMAI PEKANBARU - Sri Ayu Sundari; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Advertising is one of marketing communications media that are often used in economic activity in an effort to introduce the product to the consumer. Ads aim to achieve their positive perspective. Advertising is a source of consumer information in making purchasing decisions. The purpose of this study is to determine how much influence advertising Royco seasoning on consumer purchasing decisions housewife in Kelurahan Sidomulyo Timur Kecamatan Marpoyan Damai Pekanbaru.This research method is quantitative research methods explanatory approach to the presentation of qualitative analysis. The location of this research carried out in Kelurahan Sidomulyo Timur Kecamatan Marpoyan Damai Pekanbaru. Subjects in this study were 96 housewives who make purchases Royco seasoning category are determined by accidental sampling. The collection of data obtained through questionnaires and documentation. Data analysis techniques in this study is a quantitative analysis. The results showed that Ad Impact Royco Seasoning Seasonings Consumer Purchase Decision Against Housewife In Kelurahan Sidomulyo Timur Kecamatan Marpoyan Damai Pekanbaru. Evidenced by the regression coefficient value of this research is Y = 7915 + 0.688X. constant number of 7915 and the variable coefficient value of news for 0688. Meanwhile t 7915 is greater than the t table of 1.660, with a significance level of 0,000 is smaller than α = 0.05. According to the table "Model Summary" shows that the value of R = 0.598 and coefficient of determination (R square) is equal to 0.358. The figure shows the understanding that the contribution of the effect of variable rent Royco Seasoning Seasonings on Consumer Purchase Decision Housewife amounted to 35.80%. This means that ads Royco Seasoning Seasonings effect on Consumer Purchase Decision Housewife in Kelurahan Sidomulyo Timur Kecamatan Marpoyan Damai Pekanbaru, and the influence of the category of "enough".Keywords : ad Royco seasoning, consumer purchasing decisions